Diagnóstico e operacionalização da educação especial na Escola Lawton do meio rural ribeirinho de Breves-Pará - FERREIRA, Izanias de Sousa (2019)
The present work intends to analyze the conception and the practice of teachers on the challenge of teaching students with disabilities in “Countryside” public schools in the municipality of Breves, in the island of Marajó–Pará. In this sense, the work begins by presenting a theoretical approach about the history of Special Education in Brazil, in the municipality of Breves, and the laws and decrees that ensured and guaranteed the rights of children with disabilities. Six (6) teachers from Lawton School were interviewed to attend students with different disabilities. Teachers face daily challenges with these students, since most schools do not provide the necessary resources to develop quality work for the well-being of the learner. We also aim to know how the teaching and learning process of the special students is given, as well as to know which pedagogical actions are performed in order to achieve the desired inclusion. We base this work on the studies of Prado (2001) that explains that the learning of the different students must happen in a way that allows them a significant gain from the educational, affective and sociocultural point of view and in the Law of Guidelines and Bases (1996) that guarantees the access of students with disabilities in the school context.